ðŸ‘‰ Try now NerdPal! Our new math app on iOS and Android

# Solve the quadratic equation $-2x^2+x-1=0$

Go!
Symbolic mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

##  Final answer to the problem

$x=\frac{1+\sqrt{7}i}{4},\:x=\frac{1-\sqrt{7}i}{4}$
Got another answer? Verify it here!

##  Step-by-step Solution 

How should I solve this problem?

• Choose an option
• Solve for x
• Find the derivative using the definition
• Solve by quadratic formula (general formula)
• Simplify
• Find the integral
• Find the derivative
• Factor
• Factor by completing the square
• Find the roots
Can't find a method? Tell us so we can add it.
1

For a simpler handling of the equation, change the sign of all terms, multiplying the entire whole by $-1$

$2x^2-x-1\cdot -1=0$

Learn how to solve condensing logarithms problems step by step online.

$2x^2-x-1\cdot -1=0$

Learn how to solve condensing logarithms problems step by step online. Solve the quadratic equation -2x^2+x+-1=0. For a simpler handling of the equation, change the sign of all terms, multiplying the entire whole by -1. Multiply -1 times -1. To find the roots of a polynomial of the form ax^2+bx+c we use the quadratic formula, where in this case a=2, b=-1 and c=1. Then substitute the values of the coefficients of the equation in the quadratic formula: \displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}. Simplifying.

##  Final answer to the problem

$x=\frac{1+\sqrt{7}i}{4},\:x=\frac{1-\sqrt{7}i}{4}$

##  Explore different ways to solve this problem

Solving a math problem using different methods is important because it enhances understanding, encourages critical thinking, allows for multiple solutions, and develops problem-solving strategies. Read more

SnapXam A2

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Main Topic: Condensing Logarithms

Combining or condensing logarithms consists of rewriting a mathematical expression with several logarithms into a single logarithm, by applying the properties of logarithms.